2013
DOI: 10.5194/nhess-13-1411-2013
|View full text |Cite
|
Sign up to set email alerts
|

Early warning of snow-caused disasters in pastoral areas on the Tibetan Plateau

Abstract: This study develops a model for early warning of snow-caused livestock disasters on a county basis and proposes a method of qualitative risk assessment of snow disasters at 500 m resolution for pastoral areas on the Tibetan Plateau (TP). Data used for the model development include remote sensing data, statistical data of weather, livestock, and social economy, and 45 typical snow disaster cases from 2000 to 2010. The principal component analysis (PCA) approach is used to choose 7 crucial factors that contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 38 publications
1
34
1
Order By: Relevance
“…Simulation exper-iments using climate models indicated that, with continuing global warming, the snow cover in China would show more variations in space and time than ever before (Shi et al, 2011;Ji and Kang, 2013). Spatiotemporal variations of snow cover are also manifested as snowstorms or blizzards, particularly excessive snowfall over a short time duration (Bolsenga and Norton, 1992;Liang et al, 2008;Gao, 2009;Wang et al, 2013;Llasat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation exper-iments using climate models indicated that, with continuing global warming, the snow cover in China would show more variations in space and time than ever before (Shi et al, 2011;Ji and Kang, 2013). Spatiotemporal variations of snow cover are also manifested as snowstorms or blizzards, particularly excessive snowfall over a short time duration (Bolsenga and Norton, 1992;Liang et al, 2008;Gao, 2009;Wang et al, 2013;Llasat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Global warming has accelerated the rate of glacier melt and has increased precipitation and caused a redistribution of precipitation [39]. This increased rate of melting and precipitation has caused more frequent flooding and snow disasters [31,40]. The results also demonstrate that the snow-cover dynamics on the TP influence the atmospheric circulation and the weather system in East Asia, which further influence the climate of China [34,41,42].…”
Section: Study Areamentioning
confidence: 93%
“…The studies mainly focused on snow disaster monitoring methods [8][9][10], spatiotemporal analyses of the disaster-causing factors [7,11,12], snow disaster risk zoning and evaluation [12][13][14][15][16][17][18], and snow disaster early warning modeling and hazard assessment [1,3,[18][19][20][21][22]. Many of these studies are both qualitative and quantitative and span from hazard evaluations of snow disasters to spatiotemporal early warning systems for snow disasters, as well as from single-factor models to multi-factor models.…”
Section: Introductionmentioning
confidence: 99%
“…Snow disaster early warning includes the probabilistic prediction of the hazard area and intensity of a snow disaster that is most likely to occur in the near future. Some studies only focused on assessing prior snow-caused disasters for the factors that caused the disasters and the associated damages [2,7,18,23], the vulnerability and resilience of a hazard-bearing body [17,24] and multi-factor, comprehensive early warning models [3,21,25]. However, only a few studies intended to combine potential risk assessments of a certain area into an early warning model for snow-caused disasters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation